2017
DOI: 10.18203/2349-2902.isj20171621
|View full text |Cite
|
Sign up to set email alerts
|

Topical phenytoin dressing versus conventional dressing in diabetic ulcers

Abstract: Background: Diabetic foot ulcer is estimated to affect 15% of all diabetic individuals during their lifetime. Management requires a multisystem approach. Various techniques have been tried to treat chronic ulcers, but none was proved to be ideal.Methods: This is a prospective randomised comparative study, where 56 patients with diabetic foot ulcers admitted in dept of surgery SSG hospital, Baroda, india were divided into two comparable groups. Of which 28 underwent topical phenytoin dressings, remaining 28 und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…The mean hospital stay in the phenytoin group was 21.35±4.17 (SD) days and that in the conventional group was 27.30±6.48 (SD) days. Similar results were found by Mujeeb MMA [18] et al, they found that the mean hospital stay in the phenytoin group was 16.26±2.64 (SD) days and that in the control group was 40.97±3.31 (SD) days and Bharadva PB [19] et al that mean hospital stay in the phenytoin group was 23.96 days and that in the control group was 35 days in their respective studies. Our study found that hospital stay in phenytoin group was less than conventional group.…”
Section: Discussionsupporting
confidence: 86%
“…The mean hospital stay in the phenytoin group was 21.35±4.17 (SD) days and that in the conventional group was 27.30±6.48 (SD) days. Similar results were found by Mujeeb MMA [18] et al, they found that the mean hospital stay in the phenytoin group was 16.26±2.64 (SD) days and that in the control group was 40.97±3.31 (SD) days and Bharadva PB [19] et al that mean hospital stay in the phenytoin group was 23.96 days and that in the control group was 35 days in their respective studies. Our study found that hospital stay in phenytoin group was less than conventional group.…”
Section: Discussionsupporting
confidence: 86%